2021
DOI: 10.3390/cancers13020306
|View full text |Cite
|
Sign up to set email alerts
|

WWC Proteins: Important Regulators of Hippo Signaling in Cancer

Abstract: The Hippo signaling pathway is known to regulate cell differentiation, proliferation and apoptosis. Whereas activation of the Hippo signaling pathway leads to phosphorylation and cytoplasmic retention of the transcriptional coactivator YAP, decreased Hippo signaling results in nuclear import of YAP and subsequent transcription of pro-proliferative genes. Hence, a dynamic and precise regulation of the Hippo signaling pathway is crucial for organ size control and the prevention of tumor formation. The transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…Complete abrogation of NF2 activity results in an inability to suppress the activity of YAP/TAZ [26,27]. WWC1, WWC2, and WWC3 are another family that positively regulates the Hippo pathway via the activation of LATS1/2 [28,29]. Importantly, loss of WWC activity results in the nuclear translocation of YAP/TAZ, enabling their activation as transcription factors [28,29].…”
Section: Aripiprazole and Clozapinementioning
confidence: 99%
“…Complete abrogation of NF2 activity results in an inability to suppress the activity of YAP/TAZ [26,27]. WWC1, WWC2, and WWC3 are another family that positively regulates the Hippo pathway via the activation of LATS1/2 [28,29]. Importantly, loss of WWC activity results in the nuclear translocation of YAP/TAZ, enabling their activation as transcription factors [28,29].…”
Section: Aripiprazole and Clozapinementioning
confidence: 99%
“…In turn, the proteins of the angiomotin family (e.g., AMOT, AMOTL1 and AMOTL2) stimulate LATS1/2 activation and serve as scaffolds connecting LATS1/2 to both SAV1-MST1 and YAP [109]. Similarly, the WWC proteins function as scaffolds that stimulate LATS1/2 [110]. Clearly, these studies illustrate that Hippo is not a linear pathway but a complex network that regulates YAP/TAZ localization and stability.…”
Section: Yap Regulation: Succinct Descriptionmentioning
confidence: 95%
“…Activated LATS1/2, in complex with its regulatory protein MOB1, phosphorylates YAP and TAZ, the major downstream effectors of the Hippo pathway and novel sensors of the mevalonate and glycolytic pathways [97,104,105]. Recent studies identified other kinases and scaffolds in the Hippo pathway [106][107][108][109][110], including MAP4K1/2/3 and MAP4K4/6/7, which activate LATS1/2 and thereby lead to YAP/TAZ phosphorylation [106][107][108]. In turn, the proteins of the angiomotin family (e.g., AMOT, AMOTL1 and AMOTL2) stimulate LATS1/2 activation and serve as scaffolds connecting LATS1/2 to both SAV1-MST1 and YAP [109].…”
Section: Yap Regulation: Succinct Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the phosphorylation of downstream effector YAP (Yes-associated protein) /TAZ (Tafazzin) could be increased. Phosphorylated YAP/TAZ could be in the cytoplasm through binding 14-3-3 proteins 8 , 9 and it could promote proteasome degradation, eventually inhibiting cell proliferation 7 , 10 , 11 . However, when the cells become cancerous, Hippo pathways are suppressed.…”
Section: Introductionmentioning
confidence: 99%